Manipulating the illusion of control variations in gambling as a function of perceived control over chance outcomes - Dixon, Mark R. (2000)
The present study examined the ability to experimentally manipulate the cognitive heuristic entitled the "illusion of control". Five adult human females gambled at roulette for the oppurtunity to earn course extra-credit points. An alternating treatments design was utilized whereby in one condition subjects were allowed to select the location on the roulette board they placed their bets, and in the other condition subjects had to give their chips to the experimenter to select the location. In addition, after subjects had played the game for a number of trials, inaccurate rules related to this "illusion of control" were introduced in a multiple baseline fashion across subjects, later followed by accurate rules. Results show that the control heuristic may exist for subjects, yet that it can be brought under experimental control through the use of experimenter delivered instructions. implications for a behavior treatment of a gambling and for a within-subject approach to the study of rule-governed behavior are discussed.